ANALISIS POLA KONSUMSI POLA PANGAN BERDASASRKAN POLA PANGAN HARAPAN DI KABUPATEN MADIUN PADA TAHUN 2021 - Fadlilah Arrosyid (Birokrasi Pancasila: Jurnal Pemerintahan, Pembangunan dan Inovasi Daerah, 2022)
Food sustainability is a system consisting of sub-systems of availability, distribution, and consumption. The diversity and balance of food consumption at the family level will determine the quality of consumption at the district or city, provincial and national levels. The quality of the population's food consumption at the regional level is reflected by the Expected Food Pattern (PPH) score. The importance of keeping the PPH score is also mandated by Law (UU) Number 18 of 2012 concerning Food and Government Regulation Number 17 of 2015 concerning Food Security and Nutrition. The analysis was carried out on 450 respondents by working as farmers aged 40-49 and having an income of 1-2 million, it can be concluded that: a.) The energy consumption of the people in Madiun Regency in 2021 is 1831.5 kcal/cap/day with sufficient numbers of energy by 85.19%, where the standard of energy consumption of each person per day is 2150 kcal. b.) The protein consumption of the people of Madiun Regency in 2021 is 53.10 grams/cap/day with a protein adequacy rate of 93.19%, where the protein adequacy standard for each person per day is 57 grams/cap/day. c.) The Expected Food Pattern (PPH) score of Madiun Regency in 2021 is 83.81 with the lowest PPH score of 67.91 and the highest PPH score reaching 97.84. Therefore, to increase the PPH score in the following years, it is necessary to increase consumption in the root food group, fruit/seeds, animal food, and fruits and vegetables while the consumption of the food group must be reduced to the grain food group.